Applying the Weighted Product Method for The Best Selection of Personal Quality Control in Pt. Pacific Equinox Surabaya - M Mahaputra Hidayat; Eko Prasetyo; Sona Ahmad Susanto (JEECS (Journal of Electrical Engineering and Computer Sciences), 2020)
The aim of this research is to design and implement a decision support system software for the selection of the best quality control at PT. Pacific Equinox Surabaya. The intent and purpose of this research is to study the process of selecting the best employees who have been working on a manual system into a computerized system and use the Weighted Product method as an algorithm to facilitate the process of selecting the best employees.This system also has the advantage of helping the management process data and values of PT. Pacific Equinox Surabaya employees. In addition, more efficient time efficiency and also helps in the process of making reports required by management.The results of this study are applications that can make it easier to analyze a number of data, in order to help provide information as a result of the best employee decision making. But this system also still has weaknesses in terms of facilities and program appearance so that it still needs improvement